Single event-related changes in cerebral oxygenated hemoglobin using word game in schizophrenia - Fujiki R (Dove Medical Press, 2014)
Ryo Fujiki,1,2 Kiichiro Morita,1,2 Mamoru Sato,1,2 Yuji Yamashita,1,2 Yusuke Kato,1,2 Yohei Ishii,2 Yoshihisa Shoji,1,2 Naohisa Uchimura1 1Department of Neuropsychiatry, Kurume University, 2Cognitive and Molecular Research Institute of Brain Diseases, Kurume University School of Medicine, Kurume-City, Japan Abstract: Neuroimaging studies have been conducted using word generation tasks and have shown greater hypofrontality in patients with schizophrenia compared with healthy subjects. In this study, we compared the characteristics of oxygenated hemoglobin changes involved in both phonological and categorical verbal fluency between 35 outpatients with schizophrenia and 35 healthy subjects during a Japanese “shiritori” task using single-event-related near-infrared spectroscopy. During this task, the schizophrenic patients showed significantly smaller activation in the prefrontal cortex area than the controls. In addition, a significant positive correlation was obtained between oxygenated hemoglobin changes (prefrontal cortex area, inferior parietal area) and the severity of positive psychiatric symptoms. It is possible that hypofrontality of patients may be a diagnostic assistance tool for schizophrenia, and that the relationship between activation and positive syndrome scores may be of help in predicting functional outcome in patients. Keywords: word production task, single-event-related near-infrared spectroscopy, schizophrenia, hypofrontality, biological marker